Pembuatan Biodiesel dari Minyak Kelapa melalui Reaksi Metanolisis Menggunakan Katalis CaCO3 yang dipijarkan - Padil, Padil; Wahyuningsih, Slamet; Awaluddin, Amir (Jurnal Natur Indonesia, 2010)
Biodiesel is one of alternative fuels. Biodiesel can be made from coconut oil and is referred to as cocodiesel. Thisresearch studies the optimum condition of cocodiesel production by methanolysis reaction between coconut oiland methanol using heterogen catalyst of calcium carbonate (CaCO 3) is calcined for 1.5 hours at 900oC. In order toget optimum condition, several experimental parameters are applied such as catalyst concentration 1-3 %-wt andmolar ratio of methanol/coconut oil 4:1-12:1. The optimum condition obtained from this experimental as follow:catalyst concentration was 2%, molar ratio of methanol/coconut oil was 8:1 at 600C, produced the higgest conversionof cocodiesel 75.02%. The cocodiesel meet the requirement of Standar Nasional Indonesia (SNI) specifications.Based on data analysis, the product has a qualification as diesel fuel. SNI Biodisel is density (40 0C) 850-890Kg/m3,kinematic viscosity (40 0C) 2,3-6,0 mm2/s, cetane number min 51, iod number max 115 gr iod/100 gram,moisture content max 0,05 % volum, acid number max 0,8 mg KOH/g, flash point min 100 0C.